THE USE OF OCCUPATIONAL THERAPY FOR A CONVICTED PERSON IN PRISON, DURING THE PROBATION PERIOD - Buiciag C; Balint T. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
The probation is a complex of activities of assessment, assistance, psycho-social counseling, and surveillance inside the community of the person who is in conflict with the penal laws (guilty, charged, and convicted), aiming to reintegrate that person in society, and to protect the community from the risk of that person returning to crime. Occupational therapy represents the missing link from the social reintegration process of the freedom-deprived persons.The research hypothesis starts from the assumption that by contouring clear means for using the occupational therapy in the three basic areas (personal care, productivity, and leisure time), we can contribute to the reintegration of the individual in the social life.For this study, we selected a convicted, imprisoned subject, from the Târgu Ocna Hospital Penitentiary. The research was conducted over the course of the six months before his release on probation, as well as after his release, being assisted by the Bacău Probation Service, the subject being a resident of Bacău County.The end of our occupational therapy intervention on our subject allowed us to conclude that there were changes in his performance, and in his level of satisfaction.